New littoral mite species (Acari, Oribatida, Fortuyniidae) from the Galápagos archipelago, with ecological and zoogeographical considerations - Pfingstl, Tobias; Schatz, Heinrich (Zootaxa, 2017)
Two species of Fortuyniidae, found on the Galápagos Islands (Ecuador) are described and illustrated based on the adult and juvenile instars. Alismobates galapagoensis sp. nov. was found on six islands of the archipelago, in littoral and supralittoral habitats. It is morphologically similar to A. inexpectatus Pfingstl & Schuster, 2012 from Bermuda, but differs from that species and all other known congeners by a prominent cuticular ridge on epimeron III among other unique character combinations. Litoribates caelestis gen. and sp. nov. was found on the islands Santa Cruz and Bartolomé in the littoral zone under Maytenus and mangroves. Notes on distribution and ecological preferences of both species are included.